A power conditioning unit for high power GEO satellites based on the sequential switching shunt series regulator - Garrigos, A.; Carrasco, J.A.; Blanes, J.M.; Sanchis-Kilders, E. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
This work describes the principles of the sequential switching shunt series regulator, S4R, an innovative solution proposed by the European Space Agency and other partners to power the next generation of high power telecommunications satellites. A comparative study between, the S4R regulated bus vs. the traditional option, the sequential switching shunt regulator regulated bus -S3R regulated bus- is performed to obtain the pros and cons of both topologies in high power (>15 kW) Geosynchronous satellites